2010
DOI: 10.1021/nn100589y
|View full text |Cite
|
Sign up to set email alerts
|

Bioimaging for Targeted Delivery of Hyaluronic Acid Derivatives to the Livers in Cirrhotic Mice Using Quantum Dots

Abstract: Liver fibrosis or cirrhosis is one of the representative liver diseases with a high morbidity and mortality worldwide. Over the past decades, many kinds of antifibrotic compounds have been investigated in vitro and in vivo for the treatment of liver cirrhosis. In this work, real-time bioimaging of hyaluronic acid (HA) derivatives was carried out using quantum dots (QDots) to assess the possibility of HA derivatives as target-specific drug delivery carriers for the treatment of liver diseases. HA-QDot conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 43 publications
3
85
0
Order By: Relevance
“…The transmission pulse is 10.5 ns for Ag 2 S QDs, and 21.08 ns for CHCl 3 . The transmission pulse of nanostructure particles is much shorter than that of the laser pulse.…”
Section: Resultsmentioning
confidence: 99%
“…The transmission pulse is 10.5 ns for Ag 2 S QDs, and 21.08 ns for CHCl 3 . The transmission pulse of nanostructure particles is much shorter than that of the laser pulse.…”
Section: Resultsmentioning
confidence: 99%
“…The secretion of hepatitis C virus (HCV), the leading cause of liver cirrhosis, is reported to be highly dependent on lipoproteins [23]. In accordance with the target specific systemic delivery of HAQDot with a modification less than 25 mol% to the liver [14], siApoB/(PEI-SS)-g-HA complex was effectively delivered to the liver after tail-vein injection to Balb/c mice. The gene silencing efficiency increased up to ca.…”
Section: Target Specific Systemic Gene Silencing Of Sirna/(pei-ss)-g-mentioning
confidence: 90%
“…As a drug delivery carrier, HA has several advantages including the negligible non-specific interaction with serum components due to the polyanionic characteristics [10] and the highly efficient target specific delivery to the liver tissues with HA receptors [11e13]. According to our previous study, quantum dot labeled HA (HA-QDot) molecules were target specifically delivered to the liver and remained much longer in a cirrhotic liver than a normal liver [14]. Interestingly, the hepatocellular distribution study revealed that a large amount of HA-QDots were also delivered to HSCs as well as LSECs [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this result, they further compared the retention behavior of the conjugates in a normal and diseased liver. 75 Interestingly, it revealed that the clearance of conjugates was relatively slow in a cirrhotic liver. Furthermore, immunofluorescence and flow cytometric analyses of dissected liver tissues showed the target-specific delivery of HA derivatives to liver sinusoidal endothelial cells and hepatic stellate cells.…”
Section: Drug Molecule Trackingmentioning
confidence: 99%